PENERAPAN MODEL PROJECT BASED LEARNING (PjBL) DITINJAU DARI KEMAMPUAN BERPIKIR KREATIF PADA MATERI LUAS BANGUN DATAR SISWA KELAS V SEKOLAH DASAR - Hapsari, Wenti Tri; Sary, Ryky Mandar; Huda, Choirul (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2025)
This study aims to investigate the learning process using the Project-Based Learning (PjBL) model in relation to the creative thinking abilities of fifth-grade students on the topic of plane area. The research employed a Sequential Mixed Method with a Sequential Exploratory design. The subjects of this study were 24 fifth-grade students from SD N Panggung. Data collection instruments included an observation checklist, interview guidelines, test sheets, and a camera for documentation. The qualitative data were analyzed through four stages: data collection, data reduction, data display, and drawing conclusions. Quantitative data were analyzed using normality tests and t-tests. The results showed that during the "fundamental question" phase of PjBL syntax, students were highly enthusiastic in responding to questions. However, in the "monitoring project activity and development" phase, many groups still faced difficulties in transforming plane shapes into creative works. After the implementation of the PjBL model, there was a significant improvement in students’ creative thinking skills, as evidenced by a t-test with a significance value of 0.000. The Sig. (2-tailed) value of 0.000 < 0.05 indicates that the null hypothesis (H?) is rejected and the alternative hypothesis (H?) is accepted. Furthermore, the analysis of the application of the PjBL model in terms of creative thinking skills in the topic of plane area shows that before the implementation, there was 1 student in the “very creative” category, 11 in the “creative” category, and 12 in the “moderately creative” category. After the implementation, 14 students were categorized as “very creative” and 10 as “creative.”